Pelatihan Peningkatan Pengetahuan Seni Budaya Bagi Anak Usia Dini melalui Media Wayang Godhong - Agus Purwantoro; Sigit Purnomo Adi; Narsen Afatara (Institut Seni Indonesia Surakarta, 2023)
Early childhood (PAUD-TK) is considered a sensitive period in children, which is a period where certain functions need to be stimulated physically-motor, intellectual, social, and emotional. This form of stimulation is in the form of education and teaching in the families, communities, and schools. The effort also aims to raise the character of students, namely the subtlety of feeling (moral), which will then produce intelligence of the mind, and grow “will” power. To educate these feelings, Ki Hadjar Dewantara said that there are 2 things to go through, firstly, education on the subtleties of spiritual life which is called moral education and the second is aesthetic education. Ki Hadjar Dewantara included wayang as an aesthetic education that can smooth the feeling of beauty towards all external objects. Wayang is an ancestral heritage that is rich in artistic and cultural meaning that deserves to be introduced to early childhood. Wayang Godhong is one of them. Wayang puppets that come from godhong (leaves) of teak, tobacco, and coffee are from Gus Pur's ideas and should be introduced to children from an early age. As a result, they get to know Wayang Godhong, a unique contemporary wayang as a medium that will bring them closer to art and culture and a sense of love for nature. Through the service carried out in Magelang Regency, at PAUD Harapan Bunda Magelang, children are invited to see the manufacturing process, be directly involved in the practice of making wayang puppets using paper (and leaves), and see a simple performance by the wayang puppeteer (dalang) Pak Gus Pur.